(untitled) (Gaceta Técnica, 2016)
In recent years Venezuela has presented a crisis on the demand, commercialization and production of cement, the material needed for construction, therefor additive cements are being used without any type of regulations. This work presents the physical-mechanical characterization of three concrete mixtures with water / cement ratio of 0.45 and water / cement ratio of 0.60 with different types of Portland cement, Type I, Type CPCA1,and the third mixture corresponds to Type CPCA1 Rewarding it with a 15% addition in his own weight, developing a mixture of better quality. These concretes were characterized by: settling, setting time, percentage of total porosity, percentage of water absorption and mechanical resistance to compression. The results showed that the concrete mixture produced with CPCA1 does not meet the minimum requirements established in the Venezuelan standard for use in the elaboration of structural concrete, because among other parameters its resistance to compression it’s below the design value. As for the CPCA1 giving it 15% addition in its own weight meets the requirements, and can be used in the manufacture of concrete structural elements.